Effects of Cycloplegic Agents on Ocular Parameters in Children with Myopia and Hyperopia - Guangzhi Qu; Bingfeng Wang; Saisai Ding; Xiaocui Liu; Lei Gao; Xuli Wang (Journal of Ophthalmology)
Background. To study the effect of cycloplegia on ocular parameters in children with myopia and hyperopia. Methods. Forty-two myopia and forty-four hyperopia eyes in children between 5 and 10 years of age were included. Measurements were taken before and after cycloplegia using 1% atropine sulfate ointment. The ocular parameters included central corneal thickness (CCT), corneal curvature (CC), anterior chamber depth (ACD), pupil diameter (PD), axial length (AL), and central retinal thickness (CRT). Results. There was no significant difference in CCT, CC, and CRT between the two groups without cycloplegia, but the ACD of the myopia (3.64 ± 0.28 mm) group was significantly higher than that of hyperopia (3.40 ± 0.24 mm; t = −4.522; P<0.0001). The average PD of the myopia (4.85 ± 0.87 mm) group was significantly smaller than that of the hyperopia group (5.47 ± 1.15 mm; t = 2.903; P<0.0046). The average AL of myopia (24.25 ± 0.77 mm) was significantly higher than that of hyperopia (21.73 ± 1.24 mm; t = 12.084; P<0.0001). However, it was found that the average PD of myopia (7.68 ± 0.51 mm) was significantly larger than that of hyperopia (7.41 ± 0.57 mm; t = 2.364; P=0.0202) under cycloplegia. As for the changes in refractive factors before and after cycloplegia, deepened ACD and enlarged PD were noted in both the groups after cycloplegia. Conclusions. Cycloplegia not only affects ACD and PD but also leads to the reversal of PD differences between the two groups. Cycloplegia effects enabled us to study changes in all known ocular parameters in a short period.